Penerapan Teorema Bayes Dalam Mendiagnosa Gangguan Kepribadian Paranoid - Dwiki Putri, Dini Ridha; Fahlevi, Muhammad Reza (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Paranoid personality disorder is a condition of thought patterns and behavior that are unhealthy and different from normal people. Pervasive distrust or suspicion of other people and feel that other people are jealous of them, as a result people with this personality get limited association from their surroundings. The aim of this research is to diagnose patients with paranoid personality disorder more effectively and efficiently so that treatment can be done. The method used is Bayes' Theorem which can help analyze predetermined symptoms. The implementation of this research uses the PHP programming language and MySQL database. The level of accuracy in knowing the diagnosis on early symptoms is 84.11%, so it can be a recommendation to help psychologists diagnose paranoid personality disorders.